Mutational inactivation of the proapoptotic gene BAX confers selective advantage during tumor clonal evolution - Ionov, Yurij (The National Academy of Sciences, 2000)
A remarkable instability at simple repeated sequences characterizes gastrointestinal cancer of the microsatellite mutator phenotype (MMP). Mutations in the DNA mismatch repair gene family underlie the MMP, a landmark for hereditary nonpolyposis colorectal cancer. These tumors define a distinctive pathway for carcinogenesis because they display a particular spectrum of mutated cancer genes containing target repeats for mismatch repair deficiency. One such gene is BAX, a proapoptotic member of the Bcl-2 family of proteins, which plays a key role in programmed cell death. More than half of colon and gastric cancers of the MMP contain BAX frameshifts in a (G)(8) mononucleotide tract. However, the functional significance of these mutations in tumor progression has not been established. Here we show that inactivation of the wild-type BAX allele by de novo frameshift mutations confers a strong advantage during tumor clonal evolution. Tumor subclones with only mutant alleles frequently appeared after inoculation into nude mice of single-cell clones of colon tumor cell lines with normal alleles. In contrast, no clones of BAX-expressing cells were found after inoculation of homozygous cell clones without wild-type BAX. These results support the interpretation that BAX inactivation contributes to tumor progression by providing a survival advantage. In this context, survival analyses show that BAX mutations are indicators of poor prognosis for both colon and gastric cancer of the MMP.